Usulan Peramalan Produksi Mobil BMW dengan Jadwal Produksi Induk dan Perencanaan Material terhadap Divisi Logistic Produk Planning (Studi Kasus: PT. Tjahja Sakti Motor, Jakarta Utara) - Gidion Karo-Karo; Wahyu Eka Munardi (Universitas Bunda Mulia, 2017)
The delay of productivity process can make losses that are not small, even that losses can make the organization bankrupt. PT. Tjahja Sakti Motor do not yet have forecasting method, forecasting is only based on order BMW Indonesia. It can make the demand from the other consumer can't be fulfilled. To avoid that, they need a right forecasting method for fulfilling the demand. Researcher tries to make forecasting method that fit with demand in PT. Tjahja Sakti Motor. Researcher uses actual data demand from 2012 until 2014. After that, the researcher concluded that demand data is random demand. Therefore researcher must choose one from three forecasting method that fit with the random demand data (Simple Moving Average, Weighted Moving Average, and Exponential Smoothing). Weighted Moving Average is chosen, because have Tacking Signal with the smallest interval (-2.03 - 3.09). After decided the method of forecasting, researcher makes Master Production Planning (MPS) which breakdown to be Material Requirement Planning (MRP) with Bill Of Material (BOM) until level two.Keywords: Peramalan, Tracking Signal, MPS, MRP, BOM